2021
DOI: 10.3389/fimmu.2021.634923
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory FimA-Specific Secretory IgA Antibodies Upregulated by DC-Targeting Nasal Double DNA Adjuvant Are Essential for Elimination of Porphyromonas gingivalis

Abstract: Our previous studies showed that a combination of a DNA plasmid encoding Flt3 ligand (pFL) and CpG oligodeoxynucleotides 1826 (CpG ODN) (FL/CpG) as a nasal adjuvant provoked antigen-specific immune responses. In this study, we investigated the efficacy of a nasal vaccine consisting of FimA as the structural subunit of Porphyromonas gingivalis (P. gingivalis) fimbriae and FL/CpG for the induction of FimA-specific antibody (Ab) responses and their protective roles against nasal and lung infection by P. gingivali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Innate immune cells such as dendritic cells and adaptive immunity lymphocytes, and monocytes/macrophages localized in periodontium recognize and respond to P. gingivalis through pattern recognition receptors (PRRs), followed by the release of inflammatory cytokines and reactive oxygen species [ 18 ]. As P. gingivalis is an oral pathogen, secretory IgA antibody plays a role as the first line of defense by blocking pathogen adherence to host mucosal surfaces [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Innate immune cells such as dendritic cells and adaptive immunity lymphocytes, and monocytes/macrophages localized in periodontium recognize and respond to P. gingivalis through pattern recognition receptors (PRRs), followed by the release of inflammatory cytokines and reactive oxygen species [ 18 ]. As P. gingivalis is an oral pathogen, secretory IgA antibody plays a role as the first line of defense by blocking pathogen adherence to host mucosal surfaces [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nasal immunization of mice with ovalbumin (OVA) along with a plasmid encoding FL (pFL) as the nasal DC-targeting adjuvant reportedly induced OVA-specific SIgA and systemic IgG and IgA Ab responses [ 138 ]. The nasal administration of a combination of DNA plasmids encoding the FLT3 ligand (pFL) and CpG oligodeoxynucleotide 1826 (CpG ODN) (FL/CpG), as the nasal mucosal adjuvant, effectively enhanced the DC responses, balanced the Th1 and Th2 type cellular responses, and provided rFimA-specific IgA-based protection in the respiratory tract against Porphyromonas gingivalis [ 139 ].…”
Section: Nasal Vaccine Adjuvantsmentioning
confidence: 99%
“…The unmethylated CpG-ODNs are ligands and agonists for human and mouse toll-like receptor 9 (TLR9). When CpG-ODNs served as vaccine adjuvants, they could enhance the induction of vaccine-specific humoral and cellular immune responses [ 19 24 ]. For example, Kataoka et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kataoka et al . showed that nasal CpG-ODN effectively enhanced dendritic cells and supplied balanced rFimA-specific IgA protective immunity against P. gingivalis in the respiratory tract [ 19 ]. Khodadadi et al demonstrated that combined use of CpG-ODN adjuvant enhanced the immune protection and efficacy of a multi-epitope DNA vaccine [ 20 ].…”
Section: Introductionmentioning
confidence: 99%